PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN BAGIAN PASANG BULU MATA (studi Kasus Perusahaan Bulu Mata PT Hyup Sung Indonesia di Purbalingga) - Purwati, Erna; Fitriana, Aning (Medikonis, 2023)
The Eyelash industry companies must be able to produce products with good quality and quantity, in order to be able to survive the global market competition. The existence of scattered demands makes employees have to work extra to maximize productivity. Therefore, companies need to provide motivation and compensation in order to create balance at work. The purpose of this study is to determine the effect of compensation and motivasion can affect employee performance. This study used purposive sampling techniques and data collection using questionnaires distributed to 10 respondents. Data analysis techniques use multiple linear regression. The results of this study do not have a significant effect on employee performance, motivation does not have a significant effect on employee performance. So that in assessing the high and low performance of employees, it cannot be seen only by how much compensation and motivation they receive. In assessing employee performance, it must also be seen from various factors such as organizational culture, working environment, and job satisfaction, so that the results obtained are more accurate.